2004
DOI: 10.1007/s00105-004-0698-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapie des Pilonidalsinus und der Acne inversa

Abstract: A pilonidal sinus is a invagination of the skin over the sacrum containing a tuft of hair which enlarges by repeated friction causing the hairs to penetrate the skin. It may become symptomatic if an infection occurs. There are similarities with acne inversa, which is present in about 23% of cases. Acne inversa is an inflammation of the sebaceous glands and terminal hair follicles, chiefly in the intertriginous areas. The first manifestation can occur at any time from puberty to advanced age. 90% of patients ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
10
0
4
Order By: Relevance
“…The other histopathological changes revealed in the present study like hair fragments, acute and chronic inflammation agree with earlier descriptions [1,11,14,15,16,17,18]. Studies to date have shown that 23–30% of the patients with HS also suffer from PS [27,28]. For this reason, it is termed an ‘HS-related disorder’ [4,7,8,20,29].…”
Section: Discussionsupporting
confidence: 80%
“…The other histopathological changes revealed in the present study like hair fragments, acute and chronic inflammation agree with earlier descriptions [1,11,14,15,16,17,18]. Studies to date have shown that 23–30% of the patients with HS also suffer from PS [27,28]. For this reason, it is termed an ‘HS-related disorder’ [4,7,8,20,29].…”
Section: Discussionsupporting
confidence: 80%
“…[7][8][9][10] The other studies favored the open method as a treatment of pilonidal sinus and they depend in their conclusion on the higher rate of recurrence that appeared in the closed technique. 11,12 This difference is probably due to the inexperience or other causes of recurrence of pilonidal sinus such as obesity. 13 In present study there was no difference in the recurrence rate in both groups…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, wound related complications like secondary infection and non-healing was not observed with radiofrequency procedure. Open surgical treatment of pilonidal sinus is reported to have a very high percentage of complete wound healing (3,9,40) . However, in our study, failure of wound healing and recurrence (13%) with this procedure were noticed.…”
Section: Discussionmentioning
confidence: 99%